FRI0195 Tocilizumab infusion performed in 31 minutes in patients with rheumatoid arthritis is safe and well tolerated. (23rd January 2014) - Alperi, M.; Belmonte-Serrano, M.; Lluch, P.; Trenor, P.; Calvo-Alen, J.; García-Fernández, E.; Olivé, A.; Tinture, J.; Romero, A.
Abstract : Background: Tocilizumab (TCZ), a receptor inhibitor of IL-6, has proven effective in patients with active RA refractory to synthetic DMARDs (modifying antirheumatic drug Disease) and anti-TNF (TNF antagonists). Objectives: The study purpose was to evaluate whether a shorter infusion of tocilizumab (TCZ) time would be as safe and tolerable as the schedule suggested by the Summary of Product Characteristics (SmPC) recommendation (1 hour), by comparing 8 mg/kg (6 infusions every 4 weeks during 24 weeks) in a fast infusion time of 31 minutes (FA) vs. 1 hour (normal administration, NA) Methods: Open-label, randomized, parallel-group, multicenter pilot study in patients with moderate to severe active rheumatoid arthritis (RA). 80 patients were include, 40 on each treatment arm.Primary endpoint was incidence of infusion reactions (IR)and secondary endpoints included assessment after 24 weeks of the incidence of adverse events, EULAR response, ACR response (20%, 50% and 70%), and HAQ. Statistical analysis was performed with SAS v8, and included Student's t-test for numerical variables and Chi-Squared test for categorical data, all with a two-sided alpha error of 0.05, although study was not powered for that. Results: Out of 76 patients, 20 presented at least one IR (26.3%), none of them leading to withdrawal (22 IRs in 20.5% of FA patients vs. 24 IRs in 32.4% of NA patients), 1 patient received antihypertensive treatment before and during 1 infusion. There were not significant differences in the AEs incidence (66.7% FA vs. 81.1% NA). Four serious AEs were reported (2 per group: 5.1% FA vs. 5.4% NA): hepatitis and infection (FA), abdominal pain and Crohn's disease (NA); with only the hepatitis episode probably related to the study medication. One patient withdrew from the study because of an adverse event (thrombocytopenia of moderate intensity, probably related to the study medication). Secondary efficacy analyses included after 24 weeks 91.5% of patients achieving EULAR response (71.2% good response and 20.3% moderate response); 61.0% remission (DAS28<2.6) and 72.9% low score disease activity (DAS28<3.2); 76.8% ACR20, 63.8% ACR50, 47.8% ACR70, and 65.2% of patients with improvement of at least 0.22 units in the HAQ questionnaire Conclusions: Faster administration of tocilizumab in 31 min did not show any significant differences compared to the current recommended administration time with regards to any adverse event or any infusion reaction). The safety profile of a faster administration of tocilizumab was consistent with the results of clinical studies where a 60 minutes administration procedure was recommended. However, additional studies are necessary to confirm these results which on the other hand did not differ from those reported in similar open label trials. Disclosure of Interest: M. Alperi: None Declared, M. Belmonte-Serrano: None Declared, P. Lluch: None Declared, P. Trenor: None Declared, J. Calvo-Alen: None Declared, E. García-Fernández: None Declared, A. Olivé: None Declared, J. Tinture: None Declared, A. Romero Employee of: Roche Employee